Initial chest X-ray findings in pediatric patients diagnosed with H1N1 virus infection - Adôrno,Isa Félix (2019)
Abstract Objective: To evaluate chest X-ray findings in pediatric patients diagnosed with influenza A (H1N1) virus infection. Materials and Methods: We retrospectively reviewed chest X-ray findings in 17 cases of pulmonary infection with the H1N1 virus (in 7 males and 10 females) examined between 2012 and 2016. The mean age of the patients was 14 months (range, 2-89 months). The diagnosis was established on the basis of clinical and radiographic criteria, and the virus was detected by polymerase chain reaction. The radiographic findings were categorized by type/pattern of opacity and by lung zone. The patients were divided into two groups: those not requiring ventilatory support; and those requiring ventilatory support or evolving to death. Results: The abnormality most often seen on chest X-rays was that of peribronchovascular opacities, the majority of which affected less than 25% of the lung, the involvement being bilateral and asymmetric. The lung zone most frequently involved was the middle third, with central and peripheral distribution, without pleural effusion. There was a statistically significant difference between the groups in terms of the symmetry of pulmonary involvement, asymmetric findings predominating in the group that required ventilatory support (p = 0.029). Conclusion: In pediatric patients with H1N1 virus infection, the main alterations on the initial chest X-rays are peribronchovascular opacities, nonspecific alveolar opacities, and consolidations. Although the definitive diagnosis of H1N1 virus infection cannot be made on the basis of imaging characteristics alone, using a combination of clinical and radiographic findings can substantially improve the diagnostic accuracy.